IMPACT OF DIGITAL RADIOGRAPHY ON COLLIMATION PRACTICES IN LUMBAR SPINE IMAGING: A COMPARATIVE STUDY OF ANALOGUE AND DIGITAL TECHNIQUES - Dr. K. Harish (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
This study investigates the impact of digital radiography on collimation practices in lumbar spine imaging. A total of 120 frontal radiographs were analyzed to compare collimation accuracy between analogue and digital imaging. Findings indicate that digital radiography resulted in significantly larger irradiated fields, with 63.5 percent of the irradiated area extending beyond the region of diagnostic interest, compared to 45.2 percent in analogue radiographs. The mean irradiated field size increased by approximately 48 percent in digital images. These results suggest a decline in collimation standards following the transition to digital imaging, leading to unnecessary radiation exposure. The study emphasizes the need for improved training in collimation techniques, implementation of standardized protocols, and use of automated collimation systems. Further research is required to assess the broader impact of digital imaging on collimation across different anatomical regions and imaging modalities to ensure patient safety and radiation dose optimization.